The NIEHS Environmental Health Sciences Data Resource Portal: placing advanced technologies in service to vulnerable communities. - Pezzoli K; Tukey R; Sarabia H; Zaslavsky I; Miranda ML; Suk WA; Lin A; Ellisman M (Environmental Health Perspectives, 2007)
BACKGROUND: Two devastating hurricanes ripped across the Gulf Coast of the United States during 2005. The effects of Hurricane Katrina were especially severe: the human and environmental health impacts on New Orleans, Louisiana, and other Gulf Coast communities will be felt for decades to come. The Federal Emergency Management Agency (FEMA) estimates that Katrina's destruction disrupted the lives of roughly 650,000 Americans. Over 1,300 people died. The projected economic costs for recovery and reconstruction are likely to exceed $125 billion. OBJECTIVES: The NIEHS (National Institute of Environmental Health Sciences) Portal aims to provide decision makers with the data, information, and the tools they need to a) monitor human and environmental health impacts of disasters; b) assess and reduce human exposures to contaminants; and c) develop science-based remediation, rebuilding, and repopulation strategies. METHODS: The NIEHS Portal combines advances in geographic information systems (GIS), data mining/integration, and visualization technologies through new forms of grid-based (distributed, web-accessible) cyberinfrastructure. RESULTS: The scale and complexity of the problems presented by Hurricane Katrina made it evident that no stakeholder alone could tackle them and that there is a need for greater collaboration. The NIEHS Portal provides a collaboration-enabling, information-laden base necessary to respond to environmental health concerns in the Gulf Coast region while advancing integrative multidisciplinary research. CONCLUSIONS: The NIEHS Portal is poised to serve as a national resource to track environmental hazards following natural and man-made disasters, focus medical and environmental response and recovery resources in areas of greatest need, and function as a test bed for technologies that will help advance environmental health sciences research into the modern scientific and computing era.